Ba0.5Sr0.5Co0.8Fe0.2O3-δ / Gd0.1Ce0.9O2-δ Core/shell Nanofiber Via One-Step Electrospinning for Cathode of LT-SOFCs. (30th May 2017) - Kim, Chanho; Jang, Inyoung; Kim, Sungmin; Yoon, Heesung; Paik, Ungyu
Abstract : The cathode of solid oxide fuel cells (SOFC) is highly related with reduction of oxygen which is the critical factor for whole performance. In order to exert high power, research for improving the cathode property is needed. And reducing the expensive, complicate process is essential for accepting SOFC as future energy source. In this study, Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF)/Gd0.1 Ce0.9 O2 -δ (GDC) core/shell nanofiber which has advantages such as charge transfer, large reaction site was investigated for cathode SOFC. One step electrospinning for synthesizing heterogeneous nanofiber was employed with solution contains BSCF particles and Gd(NO3 )3, Ce(NO3 )3 indimethylformamide(DMF). Porous GDC shell surrounds the surface of BSCF nanofiber which has diameter of 200nm after sintering at 600 o C. Ideal structure for cathode which facilitates efficient path for electron and ion was fabricated.